2015
DOI: 10.1111/ahg.12129
|View full text |Cite
|
Sign up to set email alerts
|

Ficolin Gene Polymorphisms in Systemic Lupus Erythematosus and Rheumatoid Arthritis

Abstract: Systemic lupus erythemathosus (SLE) and rheumatoid arthritis (RA) are complex autoimmune diseases characterized by an immune balance breakdown and by chronic inflammation. Several findings link SLE and RA development with the complement system and ficolin components have emerged as candidates for disease development. Since genetic association studies with ficolin genes in SLE and RA have not yet been conducted in a Brazilian population, the aim of this study was to determine whether polymorphisms of ficolin-1(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Repeated or severe episodes of RF lead to permanent harm to the heart valves, bringing about rheumatic heart disease (RHD); the wellknown acquired cardiovascular disease in youth. In 2015, the prevalence of RHD was estimated to be 33,194,900 patients in RHD-endemic countries, while there were only 221,600 patients in non-endemic countries [3]. The evaluated RHD prevalence in nations with low-income and middle-income ranges from 2.7 to 51 cases per 1,000 population for clinically apparent and clinically silent RHD sequentially [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeated or severe episodes of RF lead to permanent harm to the heart valves, bringing about rheumatic heart disease (RHD); the wellknown acquired cardiovascular disease in youth. In 2015, the prevalence of RHD was estimated to be 33,194,900 patients in RHD-endemic countries, while there were only 221,600 patients in non-endemic countries [3]. The evaluated RHD prevalence in nations with low-income and middle-income ranges from 2.7 to 51 cases per 1,000 population for clinically apparent and clinically silent RHD sequentially [3].…”
Section: Introductionmentioning
confidence: 99%
“…Ficolin-3 is encoded by the FCN3 gene which is located on chromosome 1p36 and contains eight exons. Few studies showed an association between collectin and colin genes polymorphisms and infectious and autoimmune diseases [31][32][33][34][35][36]. It was shown that there are some associations between gene polymorphisms of MBL [37][38][39][40], Ficolin-1 [16], Ficolin-2 [41] [42], and MASP-2 [43] with RF.…”
Section: Introductionmentioning
confidence: 99%
“…However ficolin‐2 measurement has been shown to be strongly dependent on experimental variations and blood sample handling procedures, rendering the correlation with clinical features questionable in the absence of standardized measurement . In addition, a genetic study reported the association of ficolin‐2 gene polymorphisms with nephritis in SLE patients .…”
Section: Introductionmentioning
confidence: 99%
“…Some polymorphisms affect serum concentration of the corresponding protein and/or its structure (therefore influencing protein activity). It has been considered that certain functional variants of these genes may be associated with higher risk of development or severity of rheumatoid arthritis or rheumatic heart disease 15 , 16 , 17 , 18 …”
mentioning
confidence: 99%
“…It has been considered that certain functional variants of these genes may be associated with higher risk of development or severity of rheumatoid arthritis or rheumatic heart disease. [15][16][17][18] In some cases, arthropathy may be associated with infections. One example is reactive arthritis.…”
mentioning
confidence: 99%